Hybrid Proximal Point Algorithm for Solution of Convex Multiobjective Optimization Problem over Fixed Point Constraint: Fouzia Amir, Ali Farajzadeh, Narin Petrot - Team, Support (Thai Journal of Mathematics, 2020)
The purpose of this paper is to consider the convex constraint multiobjective optimization problem, as the constrained set is a fixed point set of nonexpansive mapping. By owing the concepts of proximal method and Mann algorithm, we introduce the algorithm and aim to establish the convergence results of the such proposed iterative algorithm to compute a solution point the considered constraint convex multiobjective optimization problem.